2022
DOI: 10.1093/ndt/gfac192
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of humoral lesions on follow-up biopsy stratifies the risk for renal graft loss after antibody-mediated rejection treatment

Abstract: Background The standard-of-care protocol, based on plasma exchanges, high-dose intravenous immunoglobulin and optimization of maintenance immunosuppression, can slow down the evolution of antibody-mediated rejection (AMR), but with high interindividual variability. Identification of a reliable predictive tool of the response to AMR treatment is a mandatory step for personalization of the follow-up strategy and to guide second-line therapies. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Bouchet et al [8 ▪ ] studied follow-up biopsies of patients treated for CAMR and observed the disappearance and progression of Banff lesions (mi, C4d) and DSA in association with CAMR. The biopsy lesion patterns fell into three groups: disappearance (30%), persistence (47%), and progression (23%).…”
Section: Pathologic Features and Outcomesmentioning
confidence: 99%
“…Bouchet et al [8 ▪ ] studied follow-up biopsies of patients treated for CAMR and observed the disappearance and progression of Banff lesions (mi, C4d) and DSA in association with CAMR. The biopsy lesion patterns fell into three groups: disappearance (30%), persistence (47%), and progression (23%).…”
Section: Pathologic Features and Outcomesmentioning
confidence: 99%